The Influence of Carbon Emission Disclosure, Corporate Social Responsibility, and Intellectual Capital on Firm Value in Coal Mining Companies in Indonesia: Pengaruh Carbon Emission Disclosure, Corporate Social Responsibility, dan Intellectual Capital Terhadap Nilai Perusahaan Batu Bara di Indonesia - Octavia Sari; Putri Wahyuni (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to analyze the significant effects of carbon emission disclosure, corporate social responsibility, and intellectual capital on firm value. The research uses quantitative approach based on secondary data. The population consists of 32 coal companies listed on the Indonesia Stock Exchange. The sampling method uses purposive sampling, which reduced the number of companies studied from 32 to 11 based on predetermined criteria. Data testing was carried out with IBM SPSS Statistics 25 through descriptive statistics, multiple regression analysis, classical assumption tests, simultaneous (F test) and partial (T test) hypothesis testing, and determination coefficient test. The results show that the carbon emission disclosure variable has a significant effect on firm value, with a t-value of 2.023 > t-table of 2.00665. Meanwhile, the corporate social responsibility variable also has a significant effect on firm value, with a t-value of 2.445 > t-table of 2.00665. The intellectual capital variable has a significant effect on firm value, with a t-value of 2.166 > t-table of 2.00665. Simultaneously, the variables of Carbon Emission Disclosure, Corporate Social Responsibility, and Intellectual Capital have a significant effect on Firm Value, with an F-value of 8.793 > F-table of 2.79 and a significance value of 0.000 < 0.05, with a regression coefficient of 30.2%.